Evaluation of anti-inflammatory activity of ethanolic extract of Gmelina arborea in experimental acute and sub-acute inflammatory models in wistar rats - Gandigawad, Priya; Poojar, Basavaraj; Hodlur, Nandan; Sori, Ravi K. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Inflammation is a complex reaction to various injurious agents such as infections, trauma, foreign bodies, tissue necrosis, physical and chemical agents, that consists of vascular responses, migration and activation of leukocytes and systemic reactions. Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) are currently the most commonly prescribed drugs for treating pain and inflammation. The traditional NSAIDs usually cause various adverse effects on long term use. Gmelina arborea Linn (Gambhari) belongs to family Verbenaceae. The roots, leaves, flowers, fruits and bark are used for treating different ailments as anthelmintic, analgesic, anti-pyretic, antidiabetic, antimicrobial, diuretic and other common disorders. Methods: The study was carried out by using inflammatory models in wistar rats. The anti-inflammatory activity of G. arborea was compared with standard drug aspirin. The study parameters for acute inflammation was assessment of reduction in inflammation & the percentage inhibition of the paw edema. The parameter for the sub-acute inflammation was percentage inhibition of the dry granuloma weight. Results: The low and high dose of G. arborea root extract significantly showed the anti-inflammatory activity when compared to control group. The high dose of G. arborea extract showed comparable results in parameters like reducing inflammation, percentage inhibition of paw edema and dry granuloma weight in acute carrageenan paw edema and sub-acute inflammation cotton pellet granuloma models with standard aspirin treated group. Conclusions: Since G. arborea root extract was having all the qualities required for anti-inflammatory drug. However, no clear inference can be drawn at this stage and hence we consider the work for further extensive research.